2015
DOI: 10.2139/ssrn.2656033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lifestyle and Cultural Values on Impulse Buying Behavior

Abstract: The aim of research is to analyze the influence of life styles and cultural values on the impulse buying behavior of Pakistani university students and professionals in different organizations. For collection of data, survey technique was used from the students of different universities and organizations by adopting the convenient sampling technique. For analyzing the group differences between the variables of lifestyles and cultural values on impulse buying behavior, it was found that only gender role has the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Impulse purchases are influenced by in-store marketing signals (Ahmed et al, 2015). Furthermore, the research revealed that prominent retail displays might influence the impulsive purchase.…”
Section: Discussionmentioning
confidence: 95%
“…Impulse purchases are influenced by in-store marketing signals (Ahmed et al, 2015). Furthermore, the research revealed that prominent retail displays might influence the impulsive purchase.…”
Section: Discussionmentioning
confidence: 95%
“…Two factors significantly influence the purchase decision, namely social factors (activity, social community, location, and future) and identity factors (work and design tastes) on home purchases simple health. Lifestyle predicts the influence on impulse buying behavior (Ahmed, 2015). When discussing lifestyle, especially in the context of purchasing decisions at online stores, differences in the lifestyle of each individual can affect decisions in making purchases at online stores in general.…”
Section: Table 1 Influence Between Variablesmentioning
confidence: 99%
“…A person's lifestyle is a pattern of one's life in daily life which is expressed in activities, interests, and opinions in question. From a marketing point of view, the lifestyle of people has differentiated themselves into different groups based on their shared interests such as their work habits, spending their time and money into different activities (Ahmed, 2015). It indicates that lifestyle and consumer purchases are interrelated.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, it is possible to find many studies in the literature examining the relationship between lifestyle and purchasing (Hinkle & Raedene, 1983;Atchariyachanvanich & Okada, 2007;Ercis et al, 2007;Lamalewa et al, 2018;Boztepe, 2018;Cugh, 2020). It is also possible to encounter lifestyle and impulse purchasing studies in different research populations (Rook, 1987;Bashir et al, 2013;Ahmed, et al, 2015;Mayasari et al, 2019;Ittaqullah et al, 2020;Wahyuni et al, 2022). However, there are limited studies available in the Turkish literature examining lifestyle and impulse purchasing behaviour.…”
mentioning
confidence: 99%
“…Bashir et al (2013) conducted a study on Pakistani university students and found that lifestyle, life satisfaction and gender had an effect on impulse purchasing behaviour. Ahmed et al (2015) concluded that lifestyle and cultural values such as life satisfaction, security, financial satisfaction, gender role and intragroup communication have an effect on impulse purchasing behaviour. Mayasari et al (2019) showed that lifestyle fashion, sales promotion and personal image of consumers exposed to mobile marketing had a positive and significant effect on impulse purchasing behaviour and customer satisfaction.…”
mentioning
confidence: 99%